COMPARATIVE STUDY ON NEWLY DEVELOPED GUAVA HYBRIDS WITH COMMERCIAL CULTIVARS UNDER MID-HILLS OF NE INDIA - N. A. DESHMUKH; P. LYNGDOH; A. K. JHA; R. K. PATEL; C. DEKA, BIDYUT (The Bioscan, 2013)
Under mid-hills of NE India, guava hybrid RCGH 1 showed upright growth habit, whereas hybrid RCGH 4, Allahabad Safeda and Lalit had semi-spreading and L 49 and RCGH 7 possess drooping growth habit. The fruit yield was recorded significantly highest RCGH 1 (39.05 kg/plant) followed by Allahabad Safeda (31.37 kg/plant), however lowest in L 49 (21.26 kg/plant) and had significantly less than RCGH 7 (24.26 kg/plant). The highest fruit weight was recorded in RCGH 4 (183.52 g). While less number of seeds/100 g fruit weight was recorded in RCGH 7 (111.18). In fruit quality hybrid RCGH 1 recorded highest TSS (10.83ºB), ascorbic acid (231.86 mg/ 100g) and total sugar (8.07%) with lowest acidity (0.50 %) followed by RCGH 7 (10.39ºB, 205.26 mg/100g, 8.05% and 0.51%), respectively, and found superior over Allahabad Safeda and L 49 under mid-hills situations